Ethical, legal, organizational and social issues related to the use of scalp cooling for the prevention of chemotherapy‐induced alopecia: A systematic review - Janet Delgado Rodríguez; Vanesa Ramos‐García; Diego Infante‐Ventura; José Carlos Suarez‐Herrera; Antonio Rueda‐Domínguez; Pedro Serrano‐Aguilar; María delMar Trujillo‐Martín (Wiley, 2023)
Abstract Introduction Scalp cooling (SC) aims to prevent chemotherapy‐induced alopecia. The goal of this systematic review is to tackle ethical, legal, organizational and social issues related to SC. Methods A critical appraisal of the literature was carried out using a systematic review design. MEDLINE, Embase and Web of Science databases were searched up until 2 June 2021. Studies addressing these aspects in English or Spanish were considered. Representatives of both patient associations and professional scientific societies related to the topic participated in the design of the protocol and the review of the findings. Results A total of 17 studies were included. Articles were critically appraised using the MMAT and SANRA. Findings were organized into four categories: (1) ethical aspects focused on equal access, gender equity and doctor-patient communication supported by Patient Decision Aids (PtDAs); (2) patient perspective and acceptability; (3) professional perspective and acceptability; (4) organizational aspects focused on accessibility and feasibility. Conclusion Cancer patients' expectations when using SC need to be adjusted to reduce the potential distress associated with hair loss. PtDAs could help patients clarify their values and preferences regarding SC. Equal access to technology should be guaranteed. Patient or Public Contribution In this systematic review, the representatives of the patient associations (Ms. María Luz Amador Muñoz of the Spanish Association Against Cancer [AECC] and Ms. Catiana Martinez Cánovas of the Spanish Breast Cancer Federation [FECMA]) participated in the review of the study protocol, as well as in the results, discussion and conclusions, making their contributions. In the type of design of these studies (systematic reviews), it is not usual to have the direct participation of patients, but in this one, we have done so, as it is a systematic review that is part of a report of the Spanish Network of Health Technology Assessment Agencies (ETS).